Paradiplomasi dalam Isu Kesetaraan Gender: Kerja Sama Pemerintah Kabupaten Jember dan Rutgers WPF Melalui Program Power to Youth (PtY) 2021-2023 [Paradiplomacy in Gender Equality Issues: Collaboration between Jember Regency Government and Rutgers WPF] - Kedhaton, Khurin; Adzmy, Muhammad Fadzryl (Jurnal Politica, 2024)
The gender inequality phenomenon is a case of human rights violation. Gender inequality makes women vulnerable to discrimination and gender-based violence. Furthermore, as a state actor, the Jember Regency government is striving to address these issues. The government collaborates with Rutgers Indonesia, a non-profit organization based in the Netherlands, to promote gender equality and reproductive health in Jember. This collaboration is carried out through the Power to Youth (PtY) program over a 5-year period (2021-2025) in two sub-districts and four villages in Jember. The program's mission is to empower adolescent girls and young women to make independent decisions and equip them with the ability to protect themselves from all forms of gender-based and sexual violence. The partnership involves reciprocal relations, categorized as paradiplomacy, between the local government and the foreign organization. The use of “Paradiplomacy” is necessary to illustrate how the collaboration between Jember Regency and Rutgers Indonesia unfolds. Through qualitative research and descriptive analysis, the author found that the paradiplomacy aligns with applicable regulations, and the regent playing a crucial role. the collaboration involves other partners addressing various challenges. The results show that the implementation of this collaboration is successful, bringing positive impacts, especially for women in Jember.